2017
DOI: 10.5539/ijbm.v12n5p192
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organisational Injustice and Counterproductive Behaviour: The Mediating Role of Work Alienation Evidence from the Egyptian Public Sector

Abstract: This study examines the relationship between the four dimensions of organisational justice, namely, distributive, procedural, interpersonal, and informational justice, and workers’ counterproductive behaviour, and whether work alienation has mediating effect in this relationship. These relationships were tested in a sample of 300 blue-collar workers operating in Egyptian public industrial context, only 236 responded positively. Results revealed that there are significant relationships between organisational in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Moreover, the study results revealed that the cynicism plays a mediating role in relationship between injustice perception and work alienation. Recently, these subjects are getting considerable attention (Dajani & Mohamad, 2017;Joe-Akunne & Oguegbe, 2019;Yıldıza & Şaylıkay, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the study results revealed that the cynicism plays a mediating role in relationship between injustice perception and work alienation. Recently, these subjects are getting considerable attention (Dajani & Mohamad, 2017;Joe-Akunne & Oguegbe, 2019;Yıldıza & Şaylıkay, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A 3-section questionnaire was designed to study the research variables. Injustice perception was measured on a scale of 4 items developed by Dajani and Mohamad (2017). Work alienation was assessed using a 5-item scale developed by Punia and Berwal (2017), while a 3-item scale adapted from Durrah, Chaudhary, and Gharib (2019) was used to assess employee's cynicism.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organizational justice, as a concept, has been operationalized in social and management sciences to depict a scenario where workers are treated without bias by the management. It is often seen as the individual's perception of fairness in actions taken by the management both internally and externally which ascertains morality in accordance with basic norms, ethics, or laws across diverse contexts and culture [1]. Epistemologically, organizational justice is traceable to France, in 1964, where it was adopted to describe employees' perception of transparency in the work place [2].…”
Section: Background To the Studymentioning
confidence: 99%